Case report: Incomplete penetrance of autosomal dominant myotonia congenita caused by a rare CLCN1 variant c.1667T>A (p.I556N) in a Malaysian family - Musa, Nurul Huda; Thilakavathy, Karuppiah; Mohamad, Nur Afiqah; Kennerson, Marina L.; Inche Mat, Liyana Najwa; Loh, Wei Chao; Abdul Rashid, Anna Misyail; Baharin, Janudin; Ibrahim, Azliza; Wan Sulaiman, Wan Aliaa; Hoo, Fan Kee; Basri, Hamidon; et al. (Frontiers in Genetics, 2023)
Myotonia congenita (MC) is a rare neuromuscular disease caused by mutations within the CLCN1 gene encoding skeletal muscle chloride channels. MC is characterized by delayed muscle relaxation during contraction, resulting in muscle stiffness. There is a lack of MC case reports and data on the prevalence among Malaysians. We report a clinical case of a 50-year-old woman presents with muscle stiffness and cramp episodes that started in early childhood. She had difficulty initiating muscle movement and presented with transient muscle weakness after rest, which usually improved after repeated contraction (warm-up phenomenon). She was diagnosed with MC after myotonic discharge on electromyography (EMG). Her brother had similar symptoms; however, no additional family members showed MC symptoms. Serum creatine kinase levels were elevated in both the proband and her brother with 447 U/L and 228 U/L recorded, respectively. Genetic analysis by whole-exome sequencing (WES) revealed a previously reported pathogenic CLCN1 gene variant c.1667T>A (p.I556N). Genetic screening of all family members revealed that the same variant was observed in the children of both the proband and her brother; however, the children did not present with either clinical or electrophysiological MC symptoms. The multiplex ligation-dependent probe amplification (MLPA) analysis conducted identified neither exon deletion nor duplication in CLCN1. In conclusion, this report describes the first case of MC in Malaysia in which incomplete penetrance observed in this family is caused by a known pathogenic CLCN1 variant.